2022
DOI: 10.1101/2022.11.28.518227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unappreciated Subcontinental Admixture in Europeans and European Americans: Implications for Genetic Epidemiology Studies

Abstract: European-ancestry populations are recognized as stratified but not as admixed, implying that residual confounding by locus-specific ancestry can affect studies of association, polygenic adaptation, and polygenic risk scores. We integrated individual-level genome-wide data from~19,000 European-ancestry individuals across 79 European populations and five European American cohorts. We generated a new reference panel that captures ancestral diversity missed by both the 1000 Genomes and Human Genome Diversity Proje… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…We demonstrated that ancestry-related differences in CNV carrier prevalence are present in both unselected community populations (UKBB) and cohorts enriched with ASD-diagnosed individuals (SPARK). We replicated the observed differences between the AFR and WB cohorts in the UKBB by comparing the AFR and EUR cohorts in SPARK, which is notable given the ascertainment differences, differing genotyping platforms ( Methods ), and presumed genetic differences between the homogeneous WB subset of the UKBB and a EUR-ancestry cohort from the United States 54 . Furthermore, SAS (UKBB) and AMR (SPARK) ancestry groups also exhibited unique patterns of CNV prevalence, demonstrating that differences in CNV carrier prevalence cannot be generalized as “EUR vs. non-EUR” differences.…”
Section: Figmentioning
confidence: 66%
“…We demonstrated that ancestry-related differences in CNV carrier prevalence are present in both unselected community populations (UKBB) and cohorts enriched with ASD-diagnosed individuals (SPARK). We replicated the observed differences between the AFR and WB cohorts in the UKBB by comparing the AFR and EUR cohorts in SPARK, which is notable given the ascertainment differences, differing genotyping platforms ( Methods ), and presumed genetic differences between the homogeneous WB subset of the UKBB and a EUR-ancestry cohort from the United States 54 . Furthermore, SAS (UKBB) and AMR (SPARK) ancestry groups also exhibited unique patterns of CNV prevalence, demonstrating that differences in CNV carrier prevalence cannot be generalized as “EUR vs. non-EUR” differences.…”
Section: Figmentioning
confidence: 66%
“…Until recently, modeling substructure in genetic data has been limited to stratifying into homogeneous groups, which either ignores finer-scale substructure or cannot be applied to populations with substantial structure (e.g., genetically admixed populations) resulting in biased results or an underuse of data (often the very data that is also underrepresented in research) 75 . Here, we show that the methods contained in the Summix2 software package can detect, adjust, and even harness substructure in summary data by estimating genetic similarity to reference groups using only summary level data.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, future studies may consider performing admixture mapping even on European‐descent individuals. Subcontinental admixture in European and European American individuals has recently been shown to influence height, LDL cholesterol, and body mass index associations with LCT , the gene responsible for human lactase production (Gouveia et al., 2023). It is clear that our current understanding of the influence of genetic admixture on phenotypes is incomplete, and further exploration of its effects in any population is warranted.…”
Section: Discussionmentioning
confidence: 99%